Chronic Elevation of Skeletal Muscle [Ca2+]i Impairs Glucose Uptake. An in Vivo and in Vitro Study - Uryash, Arkady; Mijares, Alfredo; Lopez, Carlos E.; Adams, Jose A.; Lopez, Jose R. (Frontiers in Physiology, 2022)
Skeletal muscle is the primary site of insulin-mediated glucose uptake through the body and, therefore, an essential contributor to glucose homeostasis maintenance. We have recently provided evidence that chronic elevated intracellular Ca2+ concentration at rest ([Ca2+]i) compromises glucose homeostasis in malignant hyperthermia muscle cells. To further investigate how chronic elevated muscle [Ca2+]i modifies insulin-mediated glucose homeostasis, we measured [Ca2+]i and glucose uptake in vivo and in vitro in intact polarized muscle cells from glucose-intolerant RYR1-p.R163C and db/db mice. Glucose-intolerant RYR1-p.R163C and db/db mice have significantly elevated muscle [Ca2+]i and reduced muscle glucose uptake compared to WT muscle cells. Dantrolene treatment (1.5 mg/Kg IP injection for two weeks) caused a significant reduction in fasting blood glucose levels and muscle [Ca2+]i and increased muscle glucose uptake compared to untreated RYR1-p.R163C and db/db mice. Furthermore, RYR1-p.R163C and db/db mice had abnormal basal insulin levels and response to glucose-stimulated insulin secretion. In in vitro experiments conducted on single muscle fibers, dantrolene improved insulin-mediated glucose uptake in RYR1-p.R163C and db/db muscle fibers without affecting WT muscle fibers. In muscle cells with chronic elevated [Ca2+]i, GLUT4 expression was significantly lower, and the subcellular fraction (plasma membrane/cytoplasmic) was abnormal compared to WT. The results of this study suggest that i) Chronic elevated muscle [Ca2+]i decreases insulin-stimulated glucose uptake and consequently causes hyperglycemia; ii) Reduced muscle [Ca2+]i by dantrolene improves muscle glucose uptake and subsequent hyperglycemia; iii) The mechanism by which chronic high levels of [Ca2+]i interfere with insulin action appears to involve the expression of GLUT4 and its subcellular fractionation.